The impact of trace elements and cytokines on the pathogenesis and severity of acne - Al-Isawi, S. A.; Al-Zubaidy, Z. H.; Ismaeel, G. L.; Mohsein, O. A. (Regulatory Mechanisms in Biosystems, 2025)
Acne is a multifactorial skin condition influenced by hormonal changes, microbial activity, and immune re s ponses. Recent studies highlight the roles of trace elements, such as zinc and copper, and pro-inflammatory cytokines. In this article we i nvestigate the relationship between serum trace element levels and cytokine profiles with the path o genesis and severity of acne. This case-control study was conducted from March 1 to December 1, 2024, at Nasiriyah General Hospital. It included 100 acne patients and 50 healthy controls, matched by gender and age (19 – 25 years). Blood samples (5 mL) were collected, centrifuged, and stored at – 80 °C. Inclusion criteria included acne patients aged 18–25 years and healthy controls, while exclusion criteria excluded individuals with chronic diseases or recent use of immunosuppress ors . Serum trace elements and cytokine levels were measured using atomic absorption spectroph o tometer and ELISA kits. The study found no significant difference in gender or age between acne patients and healthy controls. Acne severity was categorized as mild (35%), moderate (45%), and severe (20%). Significant differences were observed in trace element levels: zinc was lower in acne patients (50.3 ± 12.4 μg/dL) compared to controls (75.6 ± 14.3 μg/dL), while copper was higher in patients (120.4 ± 22.8 vs. 98.7 ± 19.5 μg/dL). Magnesium levels were also lower in acne patients (1. 8 ± 0.4 vs. 2.0 ± 0.3 mg/dL). Inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-8) were signi f icantly higher in patients. Correlations showed zinc, copper, and magnesium levels were associated with acne sever i ty, while cytokine levels strongly correlated with severity. This study demonstrates the significant role of trace el e ments and inflammatory cytokines in acne severity. Lower zinc and magnesium levels, along with higher copper, TNF-α, IL-1β, IL-6, and IL-8 levels in acne patients, highlight an imbalance that contributes to acne severity. The correlations between these factors suggest that targeting trace element levels and cytokine activity could offer pote n tial therapeutic strategies for managing acne.